Role of Drosophila Amyloid Precursor Protein in Memory Formation - Preat, Thomas; Goguel, Valérie (Frontiers in Molecular Neuroscience, 2016)
The amyloid precursor protein (APP) is a membrane protein engaged in complex proteolytic pathways. APP and its derivatives have been shown to play a central role in Alzheimer’s disease (AD), a progressive neurodegenerative disease characterized by memory decline. Despite huge effort from the research community, the primary cause of AD remains unclear, making it crucial to better understand the physiological role of the APP pathway in brain plasticity and memory. Drosophila melanogaster is a model system well-suited to address this issue. Although relatively simple, the fly brain is highly organized, sustains several forms of learning and memory, and drives numerous complex behaviors. Importantly, molecules and mechanisms underlying memory processes are conserved from flies to mammals. The fly encodes a single non-essential APP homolog named APP-Like (APPL). Using in vivo inducible RNA interference strategies, it was shown that APPL knockdown in the mushroom bodies—the central integrative brain structure for olfactory memory—results in loss of memory. Several APPL derivatives, such as secreted and full-length membrane APPL, may play different roles in distinct types of memory phases. Furthermore, overexpression of Drosophila amyloid peptide exacerbates the memory deficit caused by APPL knockdown, thus potentiating memory decline. Data obtained in the fly support the hypothesis that APP acts as a transmembrane receptor, and that disruption of its normal function may contribute to cognitive impairment during early AD.